Older Adults Improve on Everyday Tasks after Working Memory Training and Neurostimulation - Stephens, Jaclyn A. (Brain Stimul, 2016)
BACKGROUND: Aging is associated with decline in executive function (EF), upper-level cognitive abilities such as planning, problem solving, and working memory (WM). This decline is associated with age-related volume loss and reduced functional connectivity in the frontal lobes. Cognitive training interventions aim to counter these losses but often fail to elicit benefits beyond improvements on trained tasks. Recent interventions pairing WM training with transcranial direct current stimulation (tDCS) have improved WM and elicited transfer to untrained EF tasks. Limitations in previous work include exclusive use of laboratory-based computer training and testing and poor characterization of the mechanism(s) of durable tDCS-linked change. OBJECTIVE/HYPOTHESIS: To determine if tDCS-linked WM training improves performance on ecologically valid transfer measures administered in participants’ homes. To explore intervention-based changes using neuroimaging (fNIRS) and genotyping (COMT val158met). METHODS: 90 healthy older adult participants completed 5 sessions of WM training paired with tDCS (Sham, 1 mA tDCS, 2 mA tDCS; 15 min). At follow-up, we assessed performance change on laboratory-based and ecologically valid tasks. RESULTS: All participants showed improvement on trained tasks. Importantly, 2 mA of tDCS induced significantly greater far transfer gains after 1 month without contact. Gains were observed on standard far transfer tasks along with ecologically valid far transfer tasks, and stimulation was well tolerated by all participants. FNIRS and genotyping results were less conclusive but provide promising avenues for future research initiatives. CONCLUSION: These findings highlight the translational value for tDCS-based interventions in healthy older adults interested in maintaining cognitive function.